Risk assessment of arrhythmias related to three antiseizure medications: a systematic review and single-arm meta-analysis - Li, Yulong; Su, Shen; Zhang, Mengwen; Yu, Limin; Miao, Xinyuan; Li, Hongjun; Sun, Yanping (Frontiers in Neurology, 2024)
Objective: Antiseizure medications (ASMs) are first line therapy for seizure disorders.are recommended antiepileptic drugs. Their side effects on arrhythmias, especially specifically the risk of arrhythmias associated with lacosamide (LCM), levetiracetam (LEV), and perampanel (PER), have been intensely were investigated.We searched Ffour databases (PubMed, EMBASE, Cochrane Library, and Web of Science) were searched up until August 6, 2023. We used a common effects model and reported data as pooled proportion incidence with 95% CIs. Meta-analyseis wereas conducted to elucidate the risk of arrhythmias with different drugs, and Egger's regression was performed to detect publication bias analysis was performed.We included There are 11clinical trials withliterature, including 1031 participants, were included. The proportion pooled incidence of arrhythmias in the LEV group was 0.005 (95% CI: 0.001-0.013), while in the LCM group, it was 0.014 in the LCM group (95% CI: 0.003-0.030). The pPublication bias analyseis indicated no significantminimal bias in the LEV group (t = 0.02, df = 4, pvalue = 0.9852), while but a significant bias was observed in the LCM group (t = 5.94, df = 3, p-value = 0.0095). We corrected for this bias in the LCM group This was corrected using the trim-and-fill method, which yielded resulting in a similar pooled incidence value of 0.0137 (95% CI: 0.0036-0.0280), which was similar to the initial meta-analysis results, indicating good reliability stability. Due